An unusual case of congenital short trachea with very long bronchi mimicking bronchial asthma. Issue 4 (1st April 2002) - Ravenna, F; Caramori, G; Panella, G L; Papi, A; Benea, G; Adcock, I M; Barnes, P J; Ciaccia, A
Abstract : Case reports of a short trachea with early branching of the main bronchi are uncommon. The case is presented of a 64 year old woman with upper airway obstruction due to this anatomical abnormality which caused breathlessness and wheezing that was misdiagnosed (and treated) as bronchial asthma for many years.